Chromium films deposition by hot target high power pulsed magnetron sputtering: Deposition conditions and film properties; Surface and Coatings Technology; Vol. 375 - Grudinin V. A. Vladislav Alekseevich; Bleykher (Bleicher) G. A. Galina Alekseevna; Sidelev D. V. Dmitry Vladimirovich; Krivobokov V. P. Valery Pavlovich; Bestetti M. Massimiliano; Vicenzo A. Antonello; Franz S. Silvia (2019, 2019)
Title screen